2003
DOI: 10.3171/spi.2003.98.3.0258
|View full text |Cite
|
Sign up to set email alerts
|

Spinal meningiomas in patients younger than 50 years of age: a 21-year experience

Abstract: Object. Spinal meningiomas occur most frequently in older patients. They are well-circumscribed and slow-growing tumors that are associated with good patient outcomes following surgery. Spinal meningiomas occurring in younger patients may be more aggressive, with a worse prognosis. The authors present their 21-year experience with spinal meningiomas in patients younger than 50 years of age. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
2
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 30 publications
5
93
2
10
Order By: Relevance
“…Usually they are circumscribed and shows a slow growth and have a good post-surgical prognosis. On the other hand, the meningiomas that occur in younger patients might have an aggressive behavior and an unfavorable prognosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Usually they are circumscribed and shows a slow growth and have a good post-surgical prognosis. On the other hand, the meningiomas that occur in younger patients might have an aggressive behavior and an unfavorable prognosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Patients older than 50 years benefited moderately from surgery; 5% required reoperation for residual or recurrent tumor compared with 22% of those younger than 50 years. 17 Resection of a single eloquent nerve root involved in a nerve sheath tumor is the main risk factor related to recurrence. Other risk factors include tumor pathological pattern of schwannoma, preoperative functional status with deficit of the involved nerve root, extradural nerve sheath tumors, cervical location of the tumor, and extraradicular tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen-Gadol, et al, 3 found that rates of recurrence and reoperation in patients younger than 50 years of age were higher than those in older patients because of a higher frequency of spinal meningiomas with cervical spine locations, extradural tumor extension, and en plaque growth, all of which made total resection more difficult. Deen, et al, 4 also reported a higher rate of recurrence (20%) in patients younger than 21 years of age.…”
Section: Tumor Recurrencementioning
confidence: 99%
“…They occurred far less frequently in the cervical spine (14-27%) and only rarely in the lumbar spine (2-14%). Cohen-Gadol, et al, 3 found that in patients younger than 50 years of age there tended to be a higher frequency (39%) of spinal meningiomas located in the cervical spine, and the majority were located in the high cervical region. Levy, et al, 16 reported that tumor location varied according to sex, with significantly more thoracic spine meningiomas appearing in female patients.…”
Section: Tumor Locationsmentioning
confidence: 99%